2012
DOI: 10.1007/s10712-012-9173-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Spectral Analysis of Refined Gravity Data for Modelling the Crust–Mantle Interface and Mantle-Lithosphere Structure

Abstract: We analyse spatial and spectral characteristics of various refined gravity data used for modelling and gravimetric interpretation of the crust-mantle interface and the mantle-lithosphere structure. Depending on the purpose of the study, refined gravity data have either a strong or weak correlation with the Moho depths (Moho geometry). The compilation of the refined gravity data is purely based on available information on the crustal density structure obtained from seismic surveys without adopting any isostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Kaban et al (1999) demonstrated that the isostatic compensation does not take place only within the Earth crust but essentially also within the lithospheric mantle. This finding was later also confirmed by Kaban et al (2004) and Tenzer et al (2009Tenzer et al ( , 2012. These phenomena thus somehow limit a realistic estimation of the Moho parameters based on using only gravity data.…”
Section: Discussionmentioning
confidence: 53%
“…Kaban et al (1999) demonstrated that the isostatic compensation does not take place only within the Earth crust but essentially also within the lithospheric mantle. This finding was later also confirmed by Kaban et al (2004) and Tenzer et al (2009Tenzer et al ( , 2012. These phenomena thus somehow limit a realistic estimation of the Moho parameters based on using only gravity data.…”
Section: Discussionmentioning
confidence: 53%
“…The evaluation of δg cs from the gravity disturbance δg is based on applying the topographic and stripping gravity corrections due to major known anomalous crustal density structures. These refined gravity data should have (theoretically) a maximum correlation with the Moho geometry (Tenzer et al 2012b). However, these gravity data still comprise the long-wavelength gravity signal of unmodelled heterogeneities within the lithospheric mantle and the asthenosphere (including the core-mantle boundary zone) as well as uncertainties within the crustal model.…”
Section: Vening Meinesz-moritz Problem Of Isostasymentioning
confidence: 97%
“…The consolidated crust-stripped gravity T gradient is obtained from the corresponding gravity gradient component Trr after applying the topographic and crust density contrasts stripping gravity gradient corrections. The computation is realized according to the following scheme (Tenzer et al 2012b) (B.1) where and V are, respectively, the gravitational gradients generated by the topography and density contrasts of the ocean (bathymetry), ice, sediments and remaining anomalous density structures within the consolidated (crystalline) crust.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Stripping is often applied in geophysical studies, on global or regional scale, to unmask the signal of unknown sources, when the signal of known sources/structures can be computed (e.g. Vajda et al 2008;Tenzer et al 2009Tenzer et al , 2012a. Stripping is particularly useful in geophysical and geological investigations of the basement and the deep-seated structure beneath sedimentary basins (e.g.…”
Section: D Density Modelling and Stripped Gravity Mapmentioning
confidence: 99%